Association between an Impaired Bone Marrow Vascular Microenvironment and Prolonged Isolated Thrombocytopenia after Allogeneic Hematopoietic Stem Cell Transplantation - Yuan Kong; Yue Hu; Xiaohui Zhang; Yazhe Wang; Xiao‐Dong Mo; Yuanyuan Zhang; Yu Wang; Wei Han; Lan‐Ping Xu; Ying‐Jun Chang; Xiao‐Jun Huang (2014)
Prolonged isolated thrombocytopenia (PT) is a serious complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, it remains unclear whether abnormalities of the bone marrow (BM) microenvironment are involved in the pathogenesis of PT. This prospective, nested case-control study included 20 patients with PT, 40 matched patients with good graft function (GGF) after allo-HSCT, and 16 healthy donors (HDs). Cellular elements of the BM microenvironment, including BM endothelial cells (BMECs), perivascular cells, and endosteal cells, were analyzed via flow cytometry and via hematoxylin-eosin and immunohistochemical staining in situ. Moreover, stromal-derived factor 1 (SDF-1) and vascular endothelial growth factor (VEGF) were measured in the plasma of BM via an enzyme-linked immunosorbent assay. No significant differences in endosteal cells (15 per high-power field [hpf] versus 16 per hpf versus 20 per hpf, P > .05) were demonstrated among the patients with PT, GGF, and the HDs. The PT patients exhibited remarkable decreases in cellular elements of the vascular microenvironment, including BMECs (.01% versus .18% versus .20%, P < .0001) and perivascular cells (.01% versus .12% versus .13%, P < .0001), compared with the GGF allo-HSCT recipients and the HDs, respectively. Moreover, significantly lower levels of SDF-1 (3163 pg/mL versus 3928 pg/mL, P = .0002) and VEGF (56 pg/mL versus 123 pg/mL, P < .0001) were found in the BM plasma of the PT patients compared with the BM of the GGF patients. A multivariate analysis revealed that BMECs (odds ratio [OR] = 171.57, P = .002) and cytomegalovirus infection after HSCT (OR = 4.35, P = .009) were independent risk factors for PT. Our data suggested that an impaired BM vascular microenvironment and megakaryocyte-active factors may contribute to the occurrence of PT after HSCT.